ASSOCIATION OF GENETIC AND NON-GENETIC RISK FACTORS WITH SPECIFIC BRCA MUTATION POSITIVE BREAST CANCERS IN SOME PAKISTANI FEMALES - Malik, Samina; Hanif, Atif; Khokher, Samina; Iqbal, Zafar; Rana, Sobia; Imran, Mohammad; Bilal, Mohammad; Arslan, Mohammad (Pakistan Journal of Physiology, 2009)
Background: Breast cancer is the most common malignancy among Asian women including Pakistan where recurrent mutations among certain sub-ethnic groups predisposing to breast cancer have recently been established. Study Design: The current retrospective study involves identification of genetic and non-genetic risk factors in 27 specific mutation positive females out of a total of 100 females diagnosed with breast cancer, representing a sample from the Punjabi ethnic population of the city of Lahore. The study has been carried out by telephonic communication with the mutation positive patients or their relatives. Results: Out of the total 27% patients positive for specific BRCA mutations, 23% were positive for BRCA1 mutations and 4% for BRCA2. Among a total of 100 breast cancer patients the BRCA1-IVS14, 1G>A mutation was identified in 5 Punjabi ethnic females with Rajput subethnicity, BRCA1-3889delAG in 10 (8 with Mughal and 2 with Khan subethnicity), BRCA1-2080insA in 8 (Rajput subethnics) and BRCA2-3337C>T in 4 (Minhas subethnic) subjects. Two BRCA1 mutations, namely 3889delAG and 2080insA were found to coexist in only one study case (with Mughal subethnicity). All the mutation positive breast cancers had unilateral ductal carcinoma. Of the 23 cases positive for screened BRCA1 mutations, 17 were diagnosed for breast cancer at a relatively early age (ageâ‰¤40) and 6 were diagnosed at late age (ageâ‰¥41) whereas all cases positive for single BRCA2 mutation under consideration were diagnosed at late age. Furthermore, 24 of 27 patients with specific BRCA mutations had a positive family history of breast cancer. Conclusion: The high prevalence of the screened BRCA mutations in certain Punjabi sub-ethnicities indicates the importance of counseling. It is suggested that consanguinity may be a risk factor for recurrent population specific mutations. Hormonal factors including use of oral contraceptives, polycystic ovaries, central obesity, nulliparity, late age at first pregnancy, lack of breast feeding and activity as well as dietary factors like active or passive smoking seem to have little role in study population. Dietary factors like active or passive smoking were less likely risk factors than dietary deficiency of vitamins, especially in low income group. Anxiety and exposure to traffic pollution were additional risk factors.